The Reciprocal Relationship Between Gratitude and Life Satisfaction: Evidence From Two Longitudinal Field Studies - Unanue, Wenceslao; Gomez Mella, Marcos Esteban; Cortez, Diego Alejandro; Bravo, Diego; Araya-Véliz, Claudio; Unanue, Jesús; Van Den Broeck, Anja (Frontiers in Psychology, 2019)
Abstract Gratitude and life satisfaction are associated with several indicators of a good life (e.g. health, pro-social behavior, relationships). However, how gratitude and life satisfaction relate to each other over time has remained unknown until now. Although a substantial body of research has tested the link from gratitude to life satisfaction, the reverse association remains unexplored. In addition, recent cross-cultural research has questioned the link between gratitude and subjective well-being in non-Western countries, suggesting that the benefits of gratitude may only prevail in Western societies. However, previous cross-cultural studies have only compared Western (e.g. American) and Eastern (e.g. Asian) cultures, but this simple contrast does not adequately capture the diversity in the world. To guide further theory and practice, we therefore extended previous cross-sectional and experimental studies, by testing the bi-directional longitudinal link between gratitude and life satisfaction in a Latin American context, aiming to establish temporal precedence. We assessed two adult samples from Chile, using three-wave cross-lagged panel designs with one month (Study 1, N = 725) and three months (Study 2, N = 1841) between waves. Both studies show, for the first time, that gratitude and life satisfaction mutually predict each other over time. The reciprocal relationships suggest the existence of a virtuous circle of human well-being: higher levels of gratitude increase life satisfaction, which in turn increases gratitude, leading to a positive spiral. Key theoretical and practical implications for the dynamics of human flourishing and for the field of positive psychology are discussed.